Menjadi Manusia Spiritual-Ekologis Di Tengah Krisis Lingkungan - Sebuah Review - Frederikus Fios (Institut Teknologi Sepuluh Nopember, 2019)
Natural damage resulting from development activities committed human beings cannot be avoided. The deforestation is happening reduces the amount of forest area of Indonesia from Sabang to Merauke. The cause of the damage to our human nature as a subject of the spiritual-ecological. The materialist economic paradigm of mastering the mindset of human. The primacy of the spiritual-ecological neglected in development activities. This research aims to find an alternative relevant human models to restore nature in the midst of a crisis of the global environment and the context of Indonesia in particular. This paper is developed using the method especially ethical reflection. Finding a spiritual ecological thought as ontological basic human life in harmony with nature. Become a spiritual-ecological human being capable of providing solutions to the environmental crisis that happened an minimize the environmental crisis for the sake of ecological sustainability of creation.